2016
DOI: 10.1016/j.ypmed.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the effects of yoga on weight-related outcomes

Abstract: Introduction. Overweight and obesity are among the most important modifiable risk factors for chronic diseases and premature death. The aim of this review was to systematically assess and analyze the effects of yoga on weight-related outcomes.Methods. Medline/PubMed, Scopus, and the Cochrane Library were screened through March 2015 for randomized controlled trials on yoga for weight-related outcomes in the general population or overweight/obese individuals. Risk of bias was assessed using the Cochrane risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 136 publications
1
66
0
2
Order By: Relevance
“…Thus far, only few randomized studies have explicitly focused on the effect of yoga on anthropometric measures in overweight or obese persons. On the basis of the few available studies, recent meta-analyses showed that yoga was effective with regard to anthropometric variables in overweight or obese persons as well as in patients with type 2 diabetes or other cardiovascular risk constellations (14,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, only few randomized studies have explicitly focused on the effect of yoga on anthropometric measures in overweight or obese persons. On the basis of the few available studies, recent meta-analyses showed that yoga was effective with regard to anthropometric variables in overweight or obese persons as well as in patients with type 2 diabetes or other cardiovascular risk constellations (14,27).…”
Section: Discussionmentioning
confidence: 99%
“…Although initial evidence for the effectiveness of yoga on weight control and improved body composition from surveys (13) and clinical studies (14) is now available, the effects of yoga on abdominal obesity have not been investigated to date. Our study investigated the effect of yoga on waist circumference and further anthropometric measures in women with abdominal obesity.…”
mentioning
confidence: 99%
“…32–37 While findings from a recent review of randomized, controlled trials suggest that yoga-based interventions for overweight participants can lead to reductions in body mass index (BMI), few studies have focused on young adults. 38 Given the increasing popularity of yoga, an important question is whether yoga, as practiced by young adults in the general population, is associated with lower weight gain over time, particularly among overweight young adults.…”
Section: Introductionmentioning
confidence: 99%
“…29 Yoga is inexpensive, noninvasive, and has been determined by two comprehensive reviews of clinical trials to be a safe effective intervention to reduce BMI and effective as primary or supplemental self-care for weight loss, weight maintenance, and prevention of obesity and metabolic syndrome. 30,31 Other studies of yoga for weight loss/metabolic syndrome/diabetes have found significant reductions in abdominal obesity, 32 positive alterations in ghrelin axis, 33 and a reduction in cardiometabolic risk factors. 34 The specific mind-body approach of yoga therapy has also been found to spur psychosocial changes associated with durable weight loss, including ''yoga culture'' social support and reports that a yogic experience of weight loss was ''easier'' and ''subjects felt more confident in their ability to maintain lasting weight loss.''…”
Section: Ayurvedic Theory Obesity and Weight Lossmentioning
confidence: 99%